2018
DOI: 10.1038/s41467-018-05054-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of coexisting Dirac and triply degenerate magnons in a three-dimensional antiferromagnet

Abstract: Topological magnons are emergent quantum spin excitations featured by magnon bands crossing linearly at the points dubbed nodes, analogous to fermions in topological electronic systems. Experimental realisation of topological magnons in three dimensions has not been reported so far. Here, by measuring spin excitations (magnons) of a three-dimensional antiferromagnet Cu3TeO6 with inelastic neutron scattering, we provide direct spectroscopic evidence for the coexistence of symmetry-protected Dirac and triply deg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 67 publications
(134 reference statements)
10
73
0
Order By: Relevance
“…Motivated by this theoretical prediction, Yao et al [52] and Bao et al [53] have measured spin excitations of Cu 3 TeO 6 with inelastic neutron scattering (INS), respectively. Both of them have observed the existence of band crossing points in the magnon spectra [52,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by this theoretical prediction, Yao et al [52] and Bao et al [53] have measured spin excitations of Cu 3 TeO 6 with inelastic neutron scattering (INS), respectively. Both of them have observed the existence of band crossing points in the magnon spectra [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this theoretical prediction, Yao et al [52] and Bao et al [53] have measured spin excitations of Cu 3 TeO 6 with inelastic neutron scattering (INS), respectively. Both of them have observed the existence of band crossing points in the magnon spectra [52,53]. In addition to Dirac points, at Γ and H points of the Brillouin zone (BZ) Bao et al [53] also observed the triply degenerate nodes which can also occur in electronic bands [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…To date, gapped topological magnons in Ising-like ferromagnets have been reported in a kagome lattice material Cu(1,3bdc) [16] and in a layered honeycomb magnet CrI 3 [17]. On the other hand, magnons exhibiting symmetry protected band crossings have been found only in a single material, a three-dimensional (3D) Heisenberg antiferromagnet Cu 3 TeO 6 [18,20]. It is thus desirable to explore new test-beds with distinct spin symmetries to expand our understanding of the physics of Dirac magnons.In this paper, we present a new model 3D quantum XY magnet realizing gapless Dirac magnons, CoTiO 3 , which has a simple ilmenite crystal structure.…”
mentioning
confidence: 99%
“…Playing a central role in 3D band topology, Dirac points can, upon symmetry breaking, transition into Weyl points, line nodes or topological bandgaps with gapless surface states. Although 3D Dirac points have been experimentally discovered in electron [2][3][4][5][6][7], magnon [8,9] and photonic [10] systems along with a variety of other theoretical proposals [11][12][13][14][15][16][17][18][19][20][21][22][23], none of the surface states are topological. Specifically, there have been no robust gapless surface bands associated with the bulk Dirac points [24][25][26].…”
mentioning
confidence: 99%